On source terms and boundary conditions using arbitrary high order discontinuous Galerkin schemes - Dumbser, Michael; Munz, Claus-Dieter (Zielona Góra: Uniwersytet Zielonogórski)
This article is devoted to the discretization of source terms and boundary conditions using discontinuous Galerkin schemes with an arbitrary high order of accuracy in space and time for the solution of hyperbolic conservation laws on unstructured triangular meshes. The building block of the method is a particular numerical flux function at the element interfaces based on the solution of Generalized Riemann Problems (GRPs) with piecewise polynomial initial data.
Keywords: discontinuous Galerkin schemes; ADER approach; source terms; boundary conditions; unstructured meshes